A Pediatric Case of Diffuse Alveolar Hemorrhage Secondary to Poststreptococcal Glomerulonephritis. (20th December 2017) - Markland, Alison; Hansen, Gregory; Banks, Anke; Chibbar, Rajni; Adamko, Darryl
Abstract : This report summarizes a case of a 4-year-old girl with poststreptococcal glomerulonephritis and diffuse alveolar hemorrhage, an atypical presentation in this age group and type of vasculitic disease. We propose that her rapid improvement in clinical status was due to her treatment, continuous renal replacement therapy (CRRT). This mechanism would have impacted recovery by removing factors such as endothelial microparticles, superantigens, and immune complexes that have been postulated as the pulmonary-renal link. This may be an interesting avenue of exploration going forward given the lack of evidence in treating such conditions and emergence of CRRT.